1988
DOI: 10.3109/00365548809032465
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to Campylobacter pylori in Diverse Ethnic Groups

Abstract: Antibody response to Campylobacter pylori was measured in ethnic groups of Vietnamese, El Salvadorean and Ethiopian origin. The results were compared with the previously reported antibody titres found in sera of culture positive and culture negative patients, patients suffering from duodenal ulcer, white Australian blood donors and Australian Aboriginals. While in Vietnamese the prevalence of serologically positive sera was found to be similar to the white Australian population, numbers of serologically positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 3 publications
1
25
0
1
Order By: Relevance
“…Serologic studies suggested that the difference in the colonization rates of H. pylori was related to the ethnic backgrounds of the population studied. 24,25 In this study, the seropositive rate for preschool aboriginal children of Hsing-Yi and Jen-Ai townships in Nantou County was higher than that of any other ethnic groups. Similar observations were also reported in another study.…”
Section: Discussionmentioning
confidence: 49%
“…Serologic studies suggested that the difference in the colonization rates of H. pylori was related to the ethnic backgrounds of the population studied. 24,25 In this study, the seropositive rate for preschool aboriginal children of Hsing-Yi and Jen-Ai townships in Nantou County was higher than that of any other ethnic groups. Similar observations were also reported in another study.…”
Section: Discussionmentioning
confidence: 49%
“…Several studies have also shown that there are marked differences in the prevalence and ageSpecific frequency of Helicobacter pylori in different populations or in different ethnic groups within a definite population (5,6,23,24). However, most data that are available have been the result of the evaluation of anti-Helicobacter Pylori antibodies in serum samples obtained from Uncharacterized populations, such as blood donors (1)(2)(3)(4)(5)(6)(7)(8)(9), so that selection biases may not have been excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that there are marked differences in the prevalence and age-specific frequency of Helicobacterpylori in different populations. However, most data available have resulted largely from the evaluation of the presence of anti-Helicobacter pylori antibodies in serum samples obtained from uncharacterized populations, such as blood donors, or from subjects that were not randomly selected, so that many biases may not have been excluded (3)(4)(5)(6)(7)(8)(9). Serology has been the most widely employed method for diagnosis of Helicobacterpylori infection, since it is well suited for screening a large number of individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric colonization by the organism has been found in 33-79% of patients with functional dyspepsia (4), but similar rates are also found in symptomless individuals (5). The need for careful control of possible confounding by age, socioeconomic status, and ethnicity has been pointed out by several authors (5)(6)(7)(8)(9)(10). Since only about half of the individuals with abdominal symptoms ever see a physician for these complaints (1 l), and because the decision to consult involves selection mechanisms that may also act as confounders in the association between H. pylori and abdominal symptoms (such as socioeconomic factors, education), the role of H. pylori infection is best studied in the general population.…”
mentioning
confidence: 99%